Exploring the design space of glanceable feedback for physical activity trackers - Gouveia, Rúben; Pereira, Fábio; Karapanos, Evangelos; Munson, Sean A.; Hassenzahl, Marc (My University, 2016)
Recent research reveals over 70% of the usage of physical activity trackers to be driven by glances - brief, 5-second sessions where individuals check ongoing activity levels with no further interaction. This raises a question as to how to best design glanceable behavioral feedback. We first set out to explore the design space of glanceable feedback in physical activity trackers, which resulted in 21 unique concepts and 6 design qualities: being abstract, integrating with existing activities, supporting comparisons to targets and norms, being actionable, having the capacity to lead to checking habits and to act as a proxy to further engagement. Second, we prototyped four of the concepts and deployed them in the wild to better understand how different types of glanceable behavioral feedback affect user engagement and physical activity. We found significant differences among the prototypes, all in all, highlighting the surprisingly strong effect glanceable feedback has on individuals' behaviors.
Keywords: Behavioral feedback interfaces; Glanceable displays; Personal informatics; Physical activity tracking